Enhanced power factor of Mg2Si0.3Sn0.7 synthesized by a non-equilibrium rapid solidification method. (February 2015) - Zhang, Qiang; Zheng, Yun; Su, Xianli; Yin, Kang; Tang, Xinfeng; Uher, Ctirad
Graphical abstract: Structure homogenization achieved by melt spinning (MS) technique, rather than solid state reaction (SSR), combined with plasma activated sintering (PAS) for Mg2 Si0.3 Sn0.7 solid solution can significantly improve the carrier mobility μ, power factor PF and figure of merit ZT . Abstract : Sb-doped Mg2 Si0.3 Sn0.7 was respectively prepared by melt spinning (MS) and by a two-step solid-state reaction (SSR), followed by plasma-activated sintering (PAS). The nonequilibrium MS technique greatly improves the structural homogeneity by rapidly quenching the homogeneous melt. As a consequence, the carrier mobility and electrical conductivity is much enhanced, leading to a record power factor of 5.18 × 10 −3  W m −1  K −2 at 600 K, a 15% improvement over the SSR–PAS sample, and a high figure of merit ZT  ≈ 1.30 at 750 K.